Pasar Rebo Street Library Community Alternative Education Empowerment Model for School Out-of-School Children - Irwansyah, Muhamad; Halim, Paisal (IJESS International Journal of Education and Social Science, 2024)
The problem of dropping out of school experienced by students in Kampung Tengah, East Jakarta raised the social concern of the Pasar Rebo Street Library Community to Apply the concept of empowerment throught alternatie education activities as an effort to overcome the phenomenon of students dropping out of school. This research aims to describe the internal and external factors causing dropouts, the alternative education empowerment model and the supporting and inhibiting factors in its implementation. This research uses descriptive qualitative method with purposive sampling technique to determine informants. Data were collected throught interviews, observation and documentation. The data were analyzed using structural functionalism theory, specifically Talcott Parsons’ AGIL concept and Max Weber’s Social Action theory. The results show that the internal factor that causes children to drop out of school is the desire of children to help parents work, while the external factor is the lack of parental attention to children’s education. There are five alternative education empowerment models carried out by the Pasar Rebo Street Library Community, namely the history model of the formation of teaching staff, the book collection model for teaching materials, the student data colletction model, the student classification model and the altenative education learning model. Supporting factors in alternative education activites are motivation, commitment and a supportive environment, while the inhibiting factors are the time of organizing activities, the inconsistency of some teaching staff, and the lack of interest in learning from some students. Based on the results of the research, alternative education activities carried out by the Pasar Rebo Street Library Community for school dropouts in Kampung Tengah, East Jakarta are included in the concept of empowerment, where students are given learning, knowledge and knowledge like in formal education, and there are plans to create PKBM so that students get proof of learning or diplomas.